2016
DOI: 10.1038/ncomms10669
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the origin of giant magnetic anisotropy and fast quantum tunnelling in Rhenium(IV) single-molecule magnets

Abstract: Single-molecule magnets represent a promising route to achieve potential applications such as high-density information storage and spintronics devices. Among others, 4d/5d elements such as Re(IV) ion are found to exhibit very large magnetic anisotropy, and inclusion of this ion-aggregated clusters yields several attractive molecular magnets. Here, using ab intio calculations, we unravel the source of giant magnetic anisotropy associated with the Re(IV) ions by studying a series of mononuclear Re(IV) six coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 73 publications
3
32
0
Order By: Relevance
“…This opens the gateway to studying the pressure-dependent magnetic behaviour of the relatively large number of anisotropic, monomeric transition metal complexes which also order at low temperatures. One can imagine similarly impressive results in such systems, particularly for 5d metal ions on account of their increased magnetic anisotropy arising from their substantial spin–orbit coupling constants and the larger diffuseness of their magnetic orbitals when compared with those of the 3d and 4d ions44. Indeed the linear increase in T c with pressure seen here suggests that enhancement rates in other species may be much larger and that pressure could be employed to invoke transition from paramagnetism to LRMO.…”
Section: Discussionmentioning
confidence: 66%
“…This opens the gateway to studying the pressure-dependent magnetic behaviour of the relatively large number of anisotropic, monomeric transition metal complexes which also order at low temperatures. One can imagine similarly impressive results in such systems, particularly for 5d metal ions on account of their increased magnetic anisotropy arising from their substantial spin–orbit coupling constants and the larger diffuseness of their magnetic orbitals when compared with those of the 3d and 4d ions44. Indeed the linear increase in T c with pressure seen here suggests that enhancement rates in other species may be much larger and that pressure could be employed to invoke transition from paramagnetism to LRMO.…”
Section: Discussionmentioning
confidence: 66%
“…This has led to increased interest in the giant magnetic anisotropy offered by certain 4f/5f ions with unquenched orbital angular momenta, and selected 4d/5d metal ions possessing considerable spin-orbit coupling. 5,[7][8][9][10][11] The 5d 3 Re IV ion is characterised by large magnetic anisotropy originating from second order spin-orbit coupling, with λ ≈ 1000 cm −1 for the free ion, often resulting in large values of the axial zero field splitting parameter, D. 12,13 In addition, the diffuse nature of the 5d orbitals gives rise to significant spin delocalisation onto the ligand atoms directly bonded to it, leading to non-negligible intermolecular magnetic exchange interactions, commonly mediated by Re-X⋯ X-Re [14][15][16][17][18][19] or Re-X⋯H 2 O⋯X-Re contacts. 20 Extensive research on the hexahalorhenate moiety [Re IV X 6 ] 2− (X = F, Cl, Br or I) has shown that the magnetic behaviour of the anion in the solid state depends greatly on the nature of the cation employed.…”
Section: Introductionmentioning
confidence: 99%
“…These cause the relaxation to occur with lower energy barrier leading to smaller blocking temperature ( T B ), and is often much smaller than effective energy barrier, U eff , in SIMs. Among other factors that influence the QTM in transition‐metal SIMs, transverse components of anisotropy ( E ) play an important role in controlling QTM . Whereas, Orbach relaxation can be facilitated through higher excited states if one has strong axial ligand‐field environment around metal ions in the absence or presence of very weak transverse ligand field.…”
Section: Introductionmentioning
confidence: 99%